Evaluation of CD4 Number In HIV / AIDS Patients Who Are Running The Antiretrovial Treatment Program - Thatit Nurmawati; Yeni Kartika Sari; Aprilia Putri Hidayat (Journal of Agromedicine and Medical Sciences, 2020)
HIV is a health problem for Indonesia and the world. Enforcement of diagnoses and control efforts continue to be made to reduce the number of HIV / AIDS cases. ARVs are becoming efforts to cure HIV by increasing CD4 cell counts. CD4 cell count is a determinant of ARV therapy. The purpose of this study was to evaluate CD4 cell counts in people with HIV / AIDS who were implementing ARV programs. The study design was observational using secondary data in the form of medical record records. The study population was HIV sufferers who registered to run an HIV / AIDS antiretrovial treatment program at the Cendana Poly Ngudi Waluyo Regional Hospital in Blitar in June 2017. Samples in the study were 30 people according to inclusion and exclusion criteria with a sampling technique using a purposive sampling method. Research instruments using questionnaires. Data analysis uses descriptive method. The results showed that this CD4 cell count had a CD4 cell count of 200 cells / mm 3 by 10%, 200-499 by 90% in patients who were on ARV programs. The patient's condition and obata resistance result in a CD4 cell count not exceeding 500 mm / cell. Key words: amount CD4, ARV , patient HIV